DNA barcoding and haplotyping in different species of Andrographis. (October 2015) - Arolla, Rajender Goud; Cherukupalli, Neeraja; Khareedu, Venkateswara Rao; Vudem, Dashavantha Reddy
Abstract: The genus Andrographis, belonging to the family Acanthaceae, contains several species of medicinal importance. Species, such as Andrographis alata, Andrographis echioides, Andrographis glandulosa, Andrographis lineata, Andrographis nallamalayana and Andrographis paniculata, with several bio-active compounds are being extensively used in folk medicine. However, difference of opinion exists with regard to inclusion of the species echioides into the genus Andrographis. The present study, using rbcL and matK sequences, for the first time established DNA barcodes for these six species. The nucleotide sequence of rbcL provided species-specific haplotypes for A. alata, A. lineata, and A. paniculata . Despite the differences with regard to nucleotide sequence, all the six species showed conserved amino acid sequence. However, all the six species showed distinct haplotypes in nucleotide sequence of matK and facilitated the identification and discrimination of these species. The phylogenetic tree generated with combined sequence of rbcL and matK revealed grouping of all the six species into a single clade confirming the positioning of the species echioides into the genus Andrographis . Highlights: Developed DNA barcodes for six Andrographis species. rbcL sequence could discriminate only three species. matK sequence displayed distinct haplotypes for all six species. Phylogenetic tree showed the grouping of six species into a single clade. Resolved taxonomic ambiguity by including species echioides into genus Andrographis.